2014
DOI: 10.1016/j.celrep.2013.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Follicular Lymphoma Transformation

Abstract: Summary Follicular lymphoma (FL) is an indolent disease, but 30-40% of cases undergo histologic transformation to an aggressive malignancy, typically represented by diffuse large B cell lymphoma (DLBCL). The pathogenesis of this process remains largely unknown. Using whole-exome sequencing and copy-number analysis, here we show that the dominant clone of FL and transformed FL (tFL) arise by divergent evolution from a common mutated precursor through the acquisition of distinct genetic events. Mutations in epig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
623
1
19

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 508 publications
(672 citation statements)
references
References 47 publications
29
623
1
19
Order By: Relevance
“…Of these, CREBBP mutations were most stable throughout the course of disease, and the most significantly enriched mutations within ancestral EIPs. This is in line with prior observations that these mutations are also shared between the indolent and transformed phases of FL (13,14). In contrast, mutations within KMT2D had variable patterns of representation within diagnosis/relapse tumors from the same patient, and a lower frequency of events within EIPs across patients.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Of these, CREBBP mutations were most stable throughout the course of disease, and the most significantly enriched mutations within ancestral EIPs. This is in line with prior observations that these mutations are also shared between the indolent and transformed phases of FL (13,14). In contrast, mutations within KMT2D had variable patterns of representation within diagnosis/relapse tumors from the same patient, and a lower frequency of events within EIPs across patients.…”
Section: Discussionsupporting
confidence: 78%
“…This and other evidence therefore suggests that BCL2 translocations are not sufficient for lymphomagenesis and may be harbored in FL precursors, and that secondary genetic alterations are needed to drive clinical disease (4, 9, 10). Next-generation sequencing studies of FL have identified frequent mutation of chromatin-modifying genes (CMGs) (11)(12)(13)(14)(15). These include inactivating mutations of genes that apply activating euchromatin-associated marks [lysine-specific methyltransferase 2D (KTM2D), CREB binding protein (CREBBP), and E1A binding protein p300 (EP300)] and activating mutations within a gene that applies a repressive heterochromatin-associated mark (enhancer of zeste homolog 2, EZH2).…”
mentioning
confidence: 99%
“…In B-NHL, genetic and epigenetic alterations create tumor phenotypes that are protected against immune cytolysis. [1][2][3][4][5][6][7] Immune escape also evolves through the concerted upregulation of gene expression. 8 For example, the B-NHL subtypes FL and DLBCL upregulate the expression of genes involved in the PD1/PDL1-2 axis, the CTLA4 ligand axis, the biosynthesis of immunosuppressive Galectin 3, and the genes IDO1, VEGFA, PGE2, IL10, and HGF, among several others.…”
Section: Introductionmentioning
confidence: 99%
“…Activating genetic alterations of MYC, including genomic rearrangements, copy number gains, or amplifications, are common driving events in certain cancers. For example, acquisition of MYC alterations and subsequent upregulation of MYC and MYC target genes have been implicated as key events in the transformation of indolent follicular lymphoma (FL) to highly aggressive diffuse large B-cell lymphoma (DLBCL) and is also observed in de novo DLBCL (2,3). Alternatively, other oncogenic events drive cancer by inducing epigenetic changes that promote MYC overexpression such as in NUT midline carcinoma (NMC), a poorly differentiated, highly aggressive subtype of squamous cell carcinoma that primarily arises in midline organs (4).…”
Section: Introductionmentioning
confidence: 99%